1990
DOI: 10.1105/tpc.2.5.379
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone Synthase Promoters in Petunia Are Active in Pigmented and Unpigmented Cell Types.

Abstract: Chalcone synthase (CHS) catalyzes the first step in the biosynthesis of flavonoids that function in flower pigmentation, protection against stress, and induction of nodulation. The petunia genome contains eight complete chs genes, of which four are differentially expressed in floral tissues and UV-light-induced seedlings. The 5[prime]-flanking regions of these four chs genes were fused to the [beta]-glucuronidase (GUS) reporter gene and introduced into petunia plants by Agrobacterium-mediated transformation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 15 publications
3
64
0
Order By: Relevance
“…Binding site selection studies showed that Myb.Ph3 recognizes a consensus sequence TAACTAACAAAA (opposite strand shown; Solano et al, 1995). l h e petunia chalcone synthase J gene promoter, which directs expression of a reporter gene predominantly in epidermal cells of petunia flower buds, contains two putative MYB.Ph3 binding sites (Koes et al, 1990;Solano et al, 1995). MYB.Ph3 has been demonstrated to be a transcriptional activator of the chalcone synthase promoter in tobacco protoplasts.…”
Section: Discussionmentioning
confidence: 99%
“…Binding site selection studies showed that Myb.Ph3 recognizes a consensus sequence TAACTAACAAAA (opposite strand shown; Solano et al, 1995). l h e petunia chalcone synthase J gene promoter, which directs expression of a reporter gene predominantly in epidermal cells of petunia flower buds, contains two putative MYB.Ph3 binding sites (Koes et al, 1990;Solano et al, 1995). MYB.Ph3 has been demonstrated to be a transcriptional activator of the chalcone synthase promoter in tobacco protoplasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pigment responsible for the brown color of petunia seeds is unknown, although it can be converted into an anthocyanin (delphinidin) by treatment with mineral acid. That its synthesis requires some of the flower pigmentation loci, including an1, an11, and an6 (an6 contains the dfrA gene) (Koes et al, 1990), suggests that it may a be flavonoid polymer such as, for instance, condensed tannins or a phlobaphene. Thus, the interaction of AN1 with P1 may reflect interaction with an unknown MYB protein from petunia involved in pigmentation of the seed coat.…”
Section: An1 Represents a Bhlh Protein That Is Distinct From Jaf13 Dmentioning
confidence: 99%
“…After one day incubation at 25掳C, protein extracts were made by grinding the corolla in 400 btl 50 mM NaPi at pH 7.0, 2 mM EDTA, 20 mM DTT and 4% PVP. Luciferase activity was measured with the Luciferase Assay System (Promega Corp., WI), and GUS activity was measured as described (Koes et al 1990). Data are expressed as the ratio of arbitrary light units to arbitrary units of fluorescence.…”
Section: Plasmid Constructions Used For Transient Expression Experimentsmentioning
confidence: 99%